Analisa Kesiapan Kota Pintar (Studi Kasus Pemerintah Kota Kupang) - Liky Yuliandro Ledoh (Jurnal Inovasi Kebijakan, 2019)
. This study aims to determine the readiness of the city of Kupang as a smart city in order to help the process of compiling policies in the form of smart city master plan and road map. Smart city readiness assessment is based on guidelines from the Ministry of Communication and Information of the Republic of Indonesia based on smart readiness which has three main parameters namely enablers, drivers, and mediators. SWOT analysis is used to analyze the readiness of smart cities. The results of this study show that they are structurally quite ready, this cn be seen by see existences of infrastructure and superstructure are ready to implement smart cities. Readiness according to internal factors in the form of advantages, namely local government support, the strategic location of the city of Kupang, high economic potential, and good digital community interaction. On the other side weaknesses are weak government management, health services that have not been maximized, low public literacy, and weak environmental management. Meanwhile, from the external factors, in the form of opportunities, are central government support and the development of the industrial revolution 4.0. Furthermore the threats of the readliness of Kupang City as rapid ICT development, ICT misuse, weakened regional competitiveness, declining city quality, changes in policy at the central level and the threat of climate change.